Accelerated Dystrophy and Decay of Oligodendrocyte Precursor Cells in the APP/PS1 Model of Alzheimer’s-Like Pathology - Chacon-De-La-Rocha, Irene; Fryatt, Gemma; Rivera, Andrea D.; Verkhratsky, Alexei; Raineteau, Olivier; Gomez-Nicola, Diego; Butt, Arthur M. (Frontiers in Cellular Neuroscience, 2020)
Myelin disruption is a feature of natural aging and of Alzheimer´s disease (AD). In the CNS, myelin is produced by oligodendrocytes, which are generated throughout life by oligodendrocyte progenitor cells (OPCs). Here, we examined age-related changes in OPCs in APP/PS1 mice, a model for AD-like pathology, compared with non-transgenic (Tg) age-matched controls. Analysis was performed in the CA1 area of the hippocampus following immunolabelling for NG2 with the nuclear dye Hoescht, to identify OPC and OPC sister cells, a measure of OPC replication. The results indicate a significant decrease in the number of OPCs at 9 months in APP/PS1 mice, compared to age-matched controls, without further decline at 14 months. In addition, the number of OPC sister cells declined significantly at 14-months in APP/PS1 mice, which was not observed in age-matched controls. Notably, OPCs also displayed marked morphological changes at 14 months in APP/PS1 mice, characterized by an overall shrinkage of OPC process domains and increased process branching. The results indicate that OPC disruption is a pathological sign in the APP/PS1 mouse model of AD.